2018
DOI: 10.26804/capi.2018.02.01
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic effect in capillary pressure during the displacement process in ultra-low permeability sandstone reservoirs

Abstract: The dynamic effect in capillary pressure during the displacement process in ultra-low permeability sandstone reservoirs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Capillary pressure is an important property that can affect multiphase flow during various physical and chemical process such as petroleum recovery and CO 2 storage. [1][2][3][4] During the fluid flow process, fluid viscosity varies caused by the mixing of different kinds of fluids, which can have strong influence on the dynamic capillarity and fluid flow. 5,6 The dynamic capillarity means a dynamic effect on the capillary pressure; that is, P c -S w relationship not only depends on the fluid saturation, but also the time derivative of saturation S w ∕ t. The fluid flow behavior is correspondingly affected by the dynamic capillarity.…”
Section: Introductionmentioning
confidence: 99%
“…Capillary pressure is an important property that can affect multiphase flow during various physical and chemical process such as petroleum recovery and CO 2 storage. [1][2][3][4] During the fluid flow process, fluid viscosity varies caused by the mixing of different kinds of fluids, which can have strong influence on the dynamic capillarity and fluid flow. 5,6 The dynamic capillarity means a dynamic effect on the capillary pressure; that is, P c -S w relationship not only depends on the fluid saturation, but also the time derivative of saturation S w ∕ t. The fluid flow behavior is correspondingly affected by the dynamic capillarity.…”
Section: Introductionmentioning
confidence: 99%
“…Uniform, constant water content Moreover, it has been shown that the contact angle also changes with centrifugal acceleration and depends on drainage or imbibition and on the flow rate [47][48][49]. The alteration of either the contact angle or interface shape or dynamic effect of the matric potential [50] can change the conductance of the unsaturated pore without changing the amount of water within it, thus altering K in a violation of the DB law. This is a factor to be considered in a test using centrifugal force e.g., [51].…”
Section: Experimental Testing Of the Db Lawmentioning
confidence: 99%
“…Capillary pressure plays a vital role in multiphase flow of tight sandstone (Chen et al, 1991;Landry et al, 2014;Tang et al, 2017), it is a generic term that includes dynamic capillary pressure and static capillary pressure (Das et al, 2005;Abidoye et al, 2014;Cai et al, 2014). Recent studies indicate that dynamic capillary pressure is better than static capillary pressure concept for describing transient two-phase flow under dynamic conditions (Hassanizadeh et al, 2002;Dahle et al, 2005;Niasar et al, 2010;Bottero et al, 2011;Diamantopoulos et al, 2016;Li et al, 2018c). To study the mechanism of dynamic capillary pressure, many simulation methods are used to simulate the multiphase flow behaviors in pore-scale, including smooth particle hydrodynamic methods (Tartakovsky and Meakin, 2006;Kunz et al, 2016), fluid volume method (Blunt et al, 2002;Raeini et al, 2014), and lattice Boltzmann method (LBM).…”
Section: Introductionmentioning
confidence: 99%